Pre-operative pain sensitivity: A prediction of post-operative outcome in the obstetric population - Buhagiar, Luana Mifsud (Medknow Publications & Media Pvt Ltd, 2013)
CONTEXT: Experimental assessments can determine pain threshold and tolerance, which mirror sensitivity to pain. This, in turn, influences the post-operative experience. AIMS: The study intended to evaluate whether the pre-operative pressure and electrical pain tests can predict pain and opioid requirement following cesarean delivery. SETTINGS AND DESIGN: Research was conducted on females scheduled for cesarean section at a tertiary care hospital of the state. Twenty women were enrolled, after obtaining written informed consent. MATERIALS AND METHODS: Pain assessment was performed on the eve of cesarean sections using three devices: PainMatcher(;) determined electrical pain threshold while the algometers PainTest(™) FPN100 (manual) and PainTest(™) FPX 25 (digital) evaluated pressure pain threshold and tolerance. Post-operative pain relief included intravenous morphine administered by patient-controlled analgesia, diclofenac (100 mg, every 12 h, rectally, enforced) and paracetamol (1000 mg, every 4-6 h, orally, on patient request). Pain scores were reported on numerical rating scales at specified time intervals. STATISTICAL ANALYSIS USED: Correlational and regression statistics were computed using IBM SPSS Statistics 21 software (IBM Corporation, USA). RESULTS: A significant correlation was observed between morphine requirement and: (1) electrical pain threshold (r = -0.45, P = 0.025), (2) pressure pain threshold (r = -0.41 P = 0.036) and (3) pressure pain tolerance (r = -0.44, P = 0.026) measured by the digital algometer. The parsimonious regression model for morphine requirement consisted of electrical pain threshold (r(2)= 0.20, P = 0.049). The dose of morphine consumed within 48 h of surgery decreases by 0.9 mg for every unit increment in electrical pain threshold. CONCLUSIONS: The predictive power of pain sensitivity assessments, particularly electrical pain threshold, may portend post-cesarean outcomes, including opioid requirements.